Spectra of Nd3+ Doped Boro-Tellurite Glasses - Thyagarajan, K.; Buddhudu, S. (Asian Journal of Chemistry, 2010)
This paper reports the preparation and the absorption spectra of Nd3+ doped B2O3-BaO-TeO2-RF (R = Li, Na or K) glasses. Both physical and optical properties such as energy-level structure, bonding, oscillator-strength and radiative life times have been computed and the effects of the change in the alkali cations (Li, Na and K) in the glass chemical composition were verified.